2016
DOI: 10.24953/turkjped.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Neurological findings spectrum in Celiac disease

Abstract: We aimed to provide early diagnosis by determining possible Celiac disease related subclinical or symptomatic neurological abnormalities in children in order to decrease risk of mortality and morbidity.Children with Celiac disease were assessed with neurological examination, neurophysiological tests and neuroimaging.A total of 65 patients were included in the study. The neurological examination was abnormal in 4 patients. There were EEG abnormalities in 5 patients, VEP was abnormal in 7 patients, BAER was abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The spectrum of electroencephalography (EEG) features associated with CD is rather wide, although focal activity in terms of unilateral or bilateral spike or slow waves, mainly localized in the occipital regions, have been reported in most of the wakefulness EEG studies (Magaudda et al, 1993 ; Labate et al, 2001 ; Pratesi et al, 2003 ; Ranua et al, 2005 ; Lionetti et al, 2010 ; Licchetta et al, 2011 ; Aksoy et al, 2016 ). However, as recommended (Parisi et al, 2014 ), EEG patterns should not be considered disease-specific.…”
Section: Neurophysiological Techniques Used To Probe Cns Involvement mentioning
confidence: 99%
See 3 more Smart Citations
“…The spectrum of electroencephalography (EEG) features associated with CD is rather wide, although focal activity in terms of unilateral or bilateral spike or slow waves, mainly localized in the occipital regions, have been reported in most of the wakefulness EEG studies (Magaudda et al, 1993 ; Labate et al, 2001 ; Pratesi et al, 2003 ; Ranua et al, 2005 ; Lionetti et al, 2010 ; Licchetta et al, 2011 ; Aksoy et al, 2016 ). However, as recommended (Parisi et al, 2014 ), EEG patterns should not be considered disease-specific.…”
Section: Neurophysiological Techniques Used To Probe Cns Involvement mentioning
confidence: 99%
“…Although CD may impact the auditory system (Bürk et al, 2001 ), brainstem auditory evoked potentials (BAEPs) and vestibular evoked myogenic potentials were reported to be normal (Pawlak-Osińska et al, 2007 ). More recently, it was found that only 1 of 25 patients had abnormalities in BAEPs in terms of moderate sensorineural hearing loss (Aksoy et al, 2016 ).…”
Section: Neurophysiological Techniques Used To Probe Cns Involvement mentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, TMS changes are often subclinical (mostly referred as a “celiac iceberg”) and further studies require close monitoring of these patients because of the possibility of development of a clinically visible neurological syndrome in patients in different age sets (“symptomatic celiac disease”). The scope of the reported studies was indeed to demonstrate the increased risk of cognitive and neuropsychiatric complications in silent or atypical forms of CD, especially in patients with advanced age or those that are older during the diagnosis period [83]. It is important to note that despite their significant role, neuronal antigens and anti-ganglioside antibodies are not always associated with the neurological status and its complications in the course of CD [70,83,84].…”
Section: Discussionmentioning
confidence: 99%